2006
DOI: 10.1203/01.pdr.0000228325.24945.ac
|View full text |Cite
|
Sign up to set email alerts
|

Pentoxifylline Reduces the Incidence and Severity of Necrotizing Enterocolitis in a Neonatal Rat Model

Abstract: Necrotizing enterocolitis (NEC) is a potentially fatal illness in premature neonates. Tumor necrosis factor alpha (TNF-␣) has been shown to play a central role in the inflammatory cascade leading to the development of NEC. Published evidence points to a significant role of pentoxifylline in inhibition of TNF-␣ and in reducing mucosal injury and improving healing in ischemiareperfusion experiments. Our aim was to investigate the effect of pentoxifylline on the incidence of NEC in a neonatal rat model. Newborn S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(41 citation statements)
references
References 38 publications
(41 reference statements)
3
37
1
Order By: Relevance
“…These include anti-TNF-α [82] , PAF receptor antag onists [203] , heparin-binding EGF-like g rowth factor [204] , anti-inflammator y cytokines (IL-10) [205] , pentoxifylline [206] , intestinal trefoil factor 3 [207] , and glucagon-like peptide 2. Recent research has identified that complex glycosphingolipids in the form of gangliosides act as bioactive factors down-regulating many acute proinflammatory signals in the intestinal mucosa.…”
Section: Resultsmentioning
confidence: 99%
“…These include anti-TNF-α [82] , PAF receptor antag onists [203] , heparin-binding EGF-like g rowth factor [204] , anti-inflammator y cytokines (IL-10) [205] , pentoxifylline [206] , intestinal trefoil factor 3 [207] , and glucagon-like peptide 2. Recent research has identified that complex glycosphingolipids in the form of gangliosides act as bioactive factors down-regulating many acute proinflammatory signals in the intestinal mucosa.…”
Section: Resultsmentioning
confidence: 99%
“…With different mechanisms of action, the aim is to eliminate or to reduce the production of ROS, interleukins, tumor necrosis factor alpha (TNF-α), platelet activating factor and adhesion molecules 14,15 .…”
Section: Discussionmentioning
confidence: 99%
“…TNF-α has been demonstrated 15 . In experimental NEC model in rats, authors found that pentoxifylline was able to significantly attenuate the degree of injury to the intestinal mucosa.…”
Section: Pentoxifylline Associated To Hypertonic Saline Solution Attementioning
confidence: 99%
See 1 more Smart Citation
“…Pentoxifylline is one of these agents studied but a very weak evidence found for usage as combination therapy to antbiotics in neonatal sepsis in a Cochrane review with a relative risk of NEC of 0.62 [101] [102]. In another study which intra-peritoneal pentoxifylline used in neonatal rat model, it was found that NEC incidence and severity reduced [103]. • Amniotic fluid; In experimental animal models, in vitro proliferation and migration of gut epithelial cells was provided by both porcine and human amniotic fluid [109].…”
Section: New Medical Treatments In Researchmentioning
confidence: 99%